Go/No-Go task engagement enhances population representation of target stimuli in primary auditory cortex - Sophie Bagur (Nature Portfolio, 2018)
Sensory areas are thought to process stimulus information while higher-order processing occurs in association cortices. Here the authors report that during task engagement population activity in ferret primary auditory cortex shifts away from encoding stimulus features toward detection of the behaviourally relevant targets.